PENGEMBANGAN MEDIA PEMBELAJARAN IPS MENGGUNAKAN SPARKOL VIDEOSCRIBE TEMA KEGIATAN EKONOMI SISWA KELAS VII DI MTS MA’ARIF NU 14 SIDOREJO - Anita Anita; Triani Ratnawuri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
The purpose of this research is to produce IPS learning media using sparkol videoscribe which is valid, practical and effective to meet students' need. IPS learning media will then be tested feasibility by experts. This research uses the research procedure and development model of ADDIE. This development model consists of 5 development stages namely Analisys, Design, Development, Implementation, and Evaluation. The results showed that IPS learning media using sparkol videoscribe is feasible to use in learning. This is demonstrated by the results of the expert test on the display design of sparkol videoscribe learning media included into the criteria "Very Eligible" with a percentage of 86%, expert test results on the presentation of sparkol videoscribe learning media materials included into the criteria "Very Eligible" with a percentage of 83% and test result with small group that is 10 student to know student response to learning media of IPS using sparkol videoscribe included in criterion "Very Eligible" with percentage equal to 96%. IPS learning media using sparkol videoscribe can be used as a reference material in the subjects of social studies especially on the subject of economic activity.Keywords: IPS Learning Media, Sparkol Videoscribe